2016
DOI: 10.1109/jstqe.2016.2561201
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Mechanisms of Photobiomodulation or Low-Level Light Therapy

Abstract: Photobiomodulation (PBM) also known as low-level laser (or light) therapy (LLLT), has been known for almost 50 years but still has not gained widespread acceptance, largely due to uncertainty about the molecular, cellular, and tissular mechanisms of action. However, in recent years, much knowledge has been gained in this area, which will be summarized in this review. One of the most important chromophores is cytochrome c oxidase (unit IV in the mitochondrial respiratory chain), which contains both heme and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
873
2
72

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,069 publications
(965 citation statements)
references
References 131 publications
18
873
2
72
Order By: Relevance
“…There have been many different molecules that have been proposed over the years to act as the primary photoacceptor or chromophore in PBM [3]. The first law of photobiology states that a photon must be absorbed by a specific chromophore located inside cells or tissues to have any biological effect.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many different molecules that have been proposed over the years to act as the primary photoacceptor or chromophore in PBM [3]. The first law of photobiology states that a photon must be absorbed by a specific chromophore located inside cells or tissues to have any biological effect.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recent extensive research have focused on enhancing the repair process through strategies including the application of tissue engineered scaffolds, gene therapy, stem cell-based therapy and biophysical therapeutic intervention using light-based modality (photobiomodulation, PBM or low-level laser/light therapy, LLLT) that can promote the healing process and save patients from amputation and other severe complications [2,912]. So far, the therapies available for wound repair in immunosuppressed subjects are less effective and this has promoted us to consider about PBM therapy for effectual chronic wound care management.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cytochrome c oxidase (CCO) is a primary photoacceptor of red and near-infrared (NIR) radiation in mitochondria of cells that activates retrograde light-sensitive cellular signaling events to transport the light signal from mitochondria to nucleus, which eventually alter the cellular metabolism and functions [15]. Both scattering and absorption of light by tissue are highly wavelength-dependent and NIR light around 810–830 nm have been found to have the deepest penetration and homogeneous illumination of the full dermis and part of the hypodermis [12,15]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanism of action of laser therapy relates to the ability of damaged cells to absorb the emitted photons and transform the energy into adenosine triphosphate (ATP). Laser stimulation enhances the production of ATP by forming singlet oxygen and reactive oxygen species [15]. The lightabsorbing components of the cell are termed chromophores or photoacceptors and are contained within the mitochondria and cellular membrane.…”
Section: Discussionmentioning
confidence: 99%